Determination of Standard Activity Results of Agricultural Enterprises According to the FADN System in Central Anatolia Agricultural Basin - Kanat, Zeynep; Çelik, Yusuf (Turkish Journal of Agriculture - Food Science and Technology, 2023)
The aim of the study is to determine the types, economic size classes and standard activity results of agricultural enterprises in the Central Anatolian Agricultural Basin according to the FADN system. The research area covers 7 provinces in the Central Anatolian Basin. 9 districts representing these provinces were determined according to the purposeful sampling method. The number of sample farms from the agricultural enterprises constituting the main population in the determined districts was calculated as 292, with a 5% margin of error, within 99% confidence limits, according to the stratified random sampling method. The data collected from the sample enterprises by the survey method formed the main material of the study. Research data covers the 2016-2017 production period. In addition, secondary data were also used in the study. According to the results of the research, it was determined that the enterprises examined were in 4 farms types. These are specialist field crops, specialist grazing livestock, mixed crops-livestock, and specialist horticulture types. When the results of the farms types according to the standard income criteria are examined; The gross profit rate is 65.80% in specialized field crops farming business types, 78.80% in specialist grazing livestock farming businesses, 70.85% in mixed crops-livestock farming businesses, and 74.23% in specialist horticulture farming businesses. The net value added rate of the enterprise is 64.72% in specialist field crops farming business types, 73.48% in specialist grazing livestock farming businesses, 66.84% in mixed crops-livestock farming businesses and 65.42% in specialist horticulture farming businesses. The net farm income rate is 64.72% in specialist field crops farming business types, 73.48% in specialist grazing livestock farming businesses, 66.84% in mixed crops-livestock farming businesses and 65.42% in specialist horticulture farming businesses. It has been determined that the type of business that has a competitive advantage in terms of gross operating profit, operating net added value and net farm income criteria is specialist grazing livestock farms.